Kawasaki Disease May Increase the Risk of Subsequent Cerebrovascular Disease. Issue 4 (30th November 2021) - Lin, Chien-Heng; Lai, Jung-Nien; Lee, Inn-Chi; Chou, I-Ching; Lin, Wei-De; Lin, Mei-Chen; Hong, Syuan-Yu
Abstract : Background: Previous epidemiological investigations examining the association between Kawasaki disease (KD) and cerebrovascular disease have had conflicting results. We analyzed the association between KD and cerebrovascular disease by conducting a population-based retrospective cohort study designed to investigate the hypothesis that KD could be a risk factor for subsequent cerebrovascular disease. Methods: From the National Health Insurance Research Database of Taiwan, the data of children (aged 0–18 years old) with KD (n=8467) were collected. Starting with the first year of study observation (referred to as the baseline year), data was collected for each child with KD, and 4 non-KD patients matched for sex, urbanization level of residence, and parental occupation were randomly selected to form the non-KD cohort (n=33 868) for our analysis. For the period from January 1, 2000, to December 31, 2012, we calculated the follow-up person-years for each patient, which is the time from the index date to the diagnosis of cerebrovascular disease, death, or the end of 2012. Furthermore, we compared the incidence, the incidence rate ratio, and the 95% CI of cerebrovascular disease between the KD and non-KD cohorts. Results: The overall cerebrovascular disease incidence rate was found to be 3.19-fold higher, which is significantly higher, in the KD cohort than in the non-KD cohort (14.73 versus 4.62 per 100 000 person-years), and the overall risk of cerebrovascular disease remained higher in the KD cohort (adjusted hazard ratio, 3.16 [95% CI, 1.46–6.85]). Furthermore, children aged <5 years showed a significantly higher risk of subsequent cerebrovascular disease in the KD cohort (adjusted hazard ratio, 3.14 [95% CI, 1.43–6.92]). Conclusions: This nationwide retrospective cohort study shows that KD may increase the risk of subsequent cerebrovascular disease, especially in those with KD aged <5 years old.